Methane Emissions, Performance and Carcass Characteristics of Different Lines of Beef Steers Reared on Pasture and Finished in Feedlot - Méo-Filho, Paulo (Animals (Basel), 2020)
SIMPLE SUMMARY: The livestock sector is a significant contributor to global greenhouse gas emissions, with cattle representing 62% of CO(2) emissions. Genetic selection is a tool that has the potential to reduce emissions from rumen fermentation and can be adopted in grazing and feedlot systems. Therefore, the purpose of this study was to evaluate steers from a new line of the Canchim breed (5/8 Charolais, 3/8 Zebu) derived by genetic selection improvement, and formed and maintained as a closed herd since 1998, in regards to performance, carcass dressing, and enteric methane emissions, when compared with the old line formed and maintained as a closed herd since 1960. Animals from the new line of the Canchim breed should be used for rearing on pasture to obtain greater liveweight gain. However, genetic improvement in Canchim breed does not guarantee animals with lower methane emissions under grazing conditions. For the finishing feedlot phase, increased liveweight gain, improved feed conversion, and a better carcass dressing percentage are obtained using animals from the new line of Canchim breed. The new line also leads to higher daily feed intake and higher daily liveweight gain, but with the same methane emissions per kg of animal liveweight than the other lines. ABSTRACT: The present study aimed to investigate whether different lines of a composite breed (5/8 Charolais × 3/8 Zebu), formed at different times, and genetically improved, would result in differences in animal performance, enteric methane emissions, and carcass traits. Forty-six Canchim steers (15 months, 280 ± 33 kg liveweight) from three different lines were used: old, new, and their cross. These three breed lines were considered the treatments (arranged in four randomized blocks based on initial liveweight) and were evaluated under grazing and feedlot conditions in relation to the performance and emission of enteric methane. During the grazing period, the new line was found to be superior to the old only in relation to the average daily liveweight gain (0.692 vs. 0.547 kg/day), and with no differences in relation to the cross line (0.692 vs. 0.620). In the feedlot finishing phase, only the average daily liveweight gain was significantly higher in the new line compared to the cross and old line (1.44 vs. 1.32 and 1.23 kg/day). The new and cross lines demonstrated higher dry matter intake when compared to the old line (10.25 and 10.42 vs. 9.11 kg/day), with the crossline animals demonstrating the best feed conversion. The new line showed higher enteric methane emissions compared to the old line (178 vs. 156 g/day). The line had an effect on the carcass dressing of the animals, with greater fat thickness in carcasses from the new and cross lines than the old line (4.4 and 3.8 vs. 3.2 mm). Canchim cattle selected for improved productive performance characteristics does not guarantee animals with lower methane emissions under grazing conditions; while in feedlots, can lead to increased daily feed consumption, and hence, to higher emissions of methane.